Nanoscale synchrotron X-ray speciation of iron and calcium compounds in amyloid plaque cores from Alzheimer's disease subjects. Issue 25 (24th April 2018) - Everett, James; Collingwood, Joanna F.; Tjendana-Tjhin, Vindy; Brooks, Jake; Lermyte, Frederik; Plascencia-Villa, Germán; Hands-Portman, Ian; Dobson, Jon; Perry, George; Telling, Neil D.
Abstract : Synchrotron soft X-ray nano-imaging and spectromicroscopy reveals iron and calcium biomineralization in Alzheimer's disease amyloid plaques. Abstract : Altered metabolism of biometals in the brain is a key feature of Alzheimer's disease, and biometal interactions with amyloid-β are linked to amyloid plaque formation. Iron-rich aggregates, including evidence for the mixed-valence iron oxide magnetite, are associated with amyloid plaques. To test the hypothesis that increased chemical reduction of iron, as observed in vitro in the presence of aggregating amyloid-β, may occur at sites of amyloid plaque formation in the human brain, the nanoscale distribution and physicochemical states of biometals, particularly iron, were characterised in isolated amyloid plaque cores from human Alzheimer's disease cases using synchrotron X-ray spectromicroscopy. In situ X-ray magnetic circular dichroism revealed the presence of magnetite: a finding supported by ptychographic observation of an iron oxide crystal with the morphology of biogenic magnetite. The exceptional sensitivity and specificity of X-ray spectromicroscopy, combining chemical and magnetic probes, allowed enhanced differentiation of the iron oxides phases present. This facilitated the discovery and speciation of ferrous-rich phases and lower oxidation state phases resembling zero-valent iron as well as magnetite. Sequestered calcium was discovered in two distinct mineral forms suggesting a dynamic process of amyloid plaque calcification in vivo . The range of iron oxidation states present and the direct observation of biogenic magnetite provide unparalleled support for the hypothesis that chemical reduction of iron arises in conjunction with the formation of amyloid plaques. These new findings raise challenging questions about the relative impacts of amyloid-β aggregation, plaque formation, and disrupted metal homeostasis on the oxidative burden observed in Alzheimer's disease.